Potential biomarkers for lameness and claw lesions in dairy cows: A scoping review - Sadiq, Mohammed B.; Ramanoon, Siti Z.; Mansor, Rozaihan; Shaik Mossadeq, Wan Mastura; Syed-Hussain, Sharifah Salmah; Yimer, Nurhusien; Kaka, Ubedullah; Ajat, Mokrish; Abdullah, Jesse Faez Firdaus (Cambridge University Press, 2024)
One of the major challenges in lameness management is prompt detection, especially before visible gait disturbance. This scoping review describes the potential biomarkers for lameness in dairy cows reported in the literature, their relevance in lameness diagnosis, identifying cows at risk of developing claw lesions and monitoring recovery after treatment. Using specific keywords, a comprehensive literature search was performed in three databases: PubMed, Google Scholar and ScienceDirect to retrieve relevant articles published between 2010 and 2022. A total of 31 articles fulfilling the inclusion criteria were analysed. The categories of potential markers for lameness reported in the literature included acute phase proteins (APPs), nociceptive neuropeptides, stress hormones, proteomes, inflammatory cytokines and metabolites in serum, urine and milk. Cortisol, APPs (serum amyloid A and haptoglobin) and serum, urinary and milk metabolites were the most studied biomarkers for lameness in dairy cows. While APPs, nociceptive neuropeptides and blood cortisol analyses assisted in elucidating the pain and stress experienced by lame cows during diagnosis and after treatment, evidence-based data are lacking to support their use in identifying susceptible animals. Meanwhile, metabolomic techniques revealed promising results in assessing metabolic alterations occurring before, during and after lameness onset. Several metabolites in serum, urinary and milk were reported that could be used to identify susceptible cows even before the onset of clinical signs. Nevertheless, further research is required employing metabolomic techniques to advance our knowledge of claw horn lesions and the discovery of novel biomarkers for identifying susceptible cows. The applicability of these biomarkers is challenging, particularly in the field, as they often require invasive procedures.